Association of sarcopenia and physical activity on the severity of metabolic dysfunction-associated steatotic liver disease among United States adults: NHANES 2017 - 2018 - Wei, Xiaodie; Liu, Xiaohui; Zhao, Jinhan; Zhang, Yang; Qiu, Lixia; Zhang, Jing (Frontiers in Aging, 2025)
BackgroundSarcopenia, physical activity (PA), and sedentary behavior are associated with metabolic dysfunction-associated steatotic liver disease (MASLD). The study aimed to evaluate the effects of sarcopenia and PA on the presence and severity of MASLD.MethodsThis cross-sectional study analyzed data from the 2017-2018 National Health and Nutrition Examination Survey (NHANES). Hepatic steatosis and liver fibrosis were assessed by vibration-controlled transient elastography (VCTE). Sarcopenia was defined based on the Foundation for the National Institutes of Health criteria. PA and sedentary behavior were evaluated using the Global Physical Activity Questionnaire (GPAQ).ResultsAmong 1,831 participants, 664 were diagnosed with MASLD, including 482 with severe steatosis and 89 with significant fibrosis. The prevalence of sarcopenia in the MASLD and non-MASLD populations was 11.7% and 3.8%, respectively. Multivariable-adjusted models demonstrated that sarcopenia significantly increased the risk of MASLD (OR 2.45; 95% CI: 1.33–4.52), severe steatosis (OR 2.56; 95% CI: 1.40–4.66), and significant fibrosis (OR 6.10; 95% CI: 2.08–17.84). Additionally, individuals with sarcopenia and low PA had a 7.91-fold increased risk of developing significant fibrosis (OR, 7.91; 95% CI: 1.42–44.16, P = 0.022). Sarcopenia and prolonged sedentary behavior further increased the risk of MASLD (OR 3.75; 95% CI: 1.60–8.76), severe steatosis (OR 17.58; 95% CI: 1.93–159.79), and significant fibrosis (OR 4.32; 95% CI: 1.31–14.31).ConclusionPatients with sarcopenia should increase physical activity and reduce sedentary time to decrease the risk and progression of MASLD. Increasing muscle mass and strength through resistance exercise to reduce the risk of significant fibrosis in sarcopenia patients.